2009
DOI: 10.1177/0022219409338736
|View full text |Cite
|
Sign up to set email alerts
|

Why Elementary Teachers Might Be Inadequately Prepared to Teach Reading

Abstract: Several national reports have suggested the usefulness of systematic, explicit, synthetic phonics instruction based on English word structure along with wide reading of quality literature for supporting development in early reading instruction. Other studies have indicated, however, that many in-service teachers are not knowledgeable in the basic concepts of the English language. They may be well versed in children's literature but not know how to address the basic building blocks of language and reading. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(44 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…Educational research was not explicitly identified by them as a major source of their professional knowledge for the teaching of reading" (2007, p.68). Similar findings have been reported in the United States (Joshi, Binks, Hougen, Dahlgren, Ocker-Dean & Smith, 2009;Kilpatrick, 2015;Spear-Swerling, 2007) and in Canada (Kosnik & Beck, 2008).…”
Section: Introductionsupporting
confidence: 87%
“…Educational research was not explicitly identified by them as a major source of their professional knowledge for the teaching of reading" (2007, p.68). Similar findings have been reported in the United States (Joshi, Binks, Hougen, Dahlgren, Ocker-Dean & Smith, 2009;Kilpatrick, 2015;Spear-Swerling, 2007) and in Canada (Kosnik & Beck, 2008).…”
Section: Introductionsupporting
confidence: 87%
“…Research has highlighted that pre-service teachers recognise the importance of teaching phonics, yet they do not feel equipped to teach it effectively in the classroom (Fielding-Barnsley, 2010). Early childhood teachers generally lack the disciplinary knowledge needed to promote early language and literacy development (Cuningham et al, 2009), possibly because they have not received sufficient preparation in pre-service undergraduate courses (Joshi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Their assessment reflected foundational literacy knowledge referred to as "basic language constructs" (Binks-Cantrell, Joshi et al, 2009). Basic language constructs include aspects of phonology, morphology, phonemic awareness, and phonics.…”
Section: Measuring Teacher Knowledge Of Reading Acquisitionmentioning
confidence: 99%
“…In addition to phonology, teacher candidates should understand the association between reading and writing (McCutchen, Abbot, et al, 2002). Yet, studies show teacher preparation programs are not universally preparing teacher candidates in these areas of basic literacy concepts (Al Otaiba & Lake, 2007;Al Otaiba et al, 2012;Bos, Mather, Dickson, Podhajski, & Chard, 2001;Joshi et al, 2009;Moats et al, 2010). Given the current state of teacher knowledge related to early reading instruction, a need exists to identify evidence-based approaches to ensure teacher candidate mastery of the fundamental components of reading development.…”
mentioning
confidence: 99%